2006
DOI: 10.1007/s11127-006-9113-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on voter preferences from unrestricted choice referendums

Abstract: From 1939 to 1968 Florida used a unique referendum system to set property tax rates for public school operating expenditures at the median millage rate selected by voters. These referendums revealed the entire distribution of voter preferences, which is not possible in the standard up or down referendum. We are the first to use the Florida referendum data. The form of the ballot played an important role in how people voted. Voting machine elections were much more likely than paper ballots to result in rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…They argued that in these cases, the school board believed that the median voter desired a greater mill rate but the law prevented any higher rate. Consistent with the findings of Dunne, Reed, and Wilbanks (1997), Holcombe and Kenny (2007) also find that larger turnout decreased the likelihood of passage because high-turnout school elections, they argued, were indicative of strongly negative feelings about the district. In sum, successful districts paid close attention to the desires of the potential voter population.…”
Section: Taxes and Satisfactionsupporting
confidence: 83%
See 1 more Smart Citation
“…They argued that in these cases, the school board believed that the median voter desired a greater mill rate but the law prevented any higher rate. Consistent with the findings of Dunne, Reed, and Wilbanks (1997), Holcombe and Kenny (2007) also find that larger turnout decreased the likelihood of passage because high-turnout school elections, they argued, were indicative of strongly negative feelings about the district. In sum, successful districts paid close attention to the desires of the potential voter population.…”
Section: Taxes and Satisfactionsupporting
confidence: 83%
“…Fort and Bunn (1998) found that requesting the funds that the median voter would approve increased the chances of passage. Using unique data from Florida where voters could write in mill rates if they did not like the school board's proposal, Holcombe and Kenny (2007) found that districts that proposed the highest legal mill rate (10 mills) were more successful than were those districts that proposed other rates. They argued that in these cases, the school board believed that the median voter desired a greater mill rate but the law prevented any higher rate.…”
Section: Taxes and Satisfactionmentioning
confidence: 99%
“…Data on the distribution of votes cast in these referendums were not systematically retained, so in a data collection procedure more thoroughly described in Holcombe and Kenny (2007) we obtained data on individual referendums from a combination of the Florida Department of Elections, county election supervisors, and the minutes of school board meetings. Most of the referendum outcome data came from school board minutes.…”
Section: Florida's Unique Referendum Systemmentioning
confidence: 99%
“…This is the first test of Romer and Romer's hypothesis that is based on a comparison of spending in referendum states having the restricted choice setting they model with spending in a referendum state that gave voters unrestricted choice, guaranteeing the spending preferred by the median voter. This setting provides a clean test of Romer and Rosenthal's prediction. The details on the operation of Florida's unrestricted choice referendum process are described in Holcombe (1977) and Holcombe and Kenny (2007), but essentially the system worked this way. The level of public school operational expenditures was determined by the voters in referendums held every two years.…”
mentioning
confidence: 99%
“…While I use this variable as a measure of support for public schools, it should be noted that the relationship between property taxes, school referenda, and school spending is likely more complicated. See Fischel () and Holcombe and Kenny ().…”
mentioning
confidence: 99%